Multidimensionalidade da pobreza subjetiva e suas implicações na construção da escala de pobreza subjetiva (EPSub) - Barbosa, Vilkiane Natercia Malherme (2024)
This study deals with understanding the construct of subjective poverty. There is no consensus on its conceptualisation or how to measure it. It has been analysed essentially from two perspectives: one that recognises it as a dimension of poverty, from a multidimensional perspective, and another that understands it as a line of measurement from a monetary perspective. In this sen se, the starting questions are as follows: How is subjective poverty constituted? How can a measure of subjective poverty be constructed? Thus, the general aim of the thesis is to understand how the construct of subjective poverty is constituted and measur ed, and the specific aims are: to define the theoretical structure of the construct of subjective poverty; to identify cognitive perceptions, behaviours or feelings related to subjective poverty; to construct an instrument to measure subjective poverty; an d, to identify patterns of interaction between the construct of subjective poverty and sociodemographic variables; to reflect on the differences between subjective poverty and subjective well being. The mixed method is the strategy used. The participants w ere university students from public and private institutions in the city of Fortaleza. The qualitative stage of the study consisted of analysing focus groups using Critical Discourse Analysis. The quantitative stage was carried out in two separate stages. In the first stage, a sociodemographic questionnaire was applied with items eligible for the Subjective Poverty Scale, which were analysed by Exploratory Factor Analysis. In the second stage, the scale was applied based on the findings of the first applica tion to carry out the Confirmatory Factor Analysis. Measures of subjective well being and social desirability were also included for correlation and regression analyses. In addition, descriptive analyses and comparative analyses of means with sociodemograp hic variables were carried out in both stages. The results point to a theoretical and instrumental structure of SP aligned with the perspective of self perception of poverty and the feeling of poverty. In addition, the socioeconomic position in which the s ubject is inserted is important for understanding whether they are in more or less subjective poverty. And the more PS is Abstract RESUMORESRE present, the less subjective well present, the less subjective well--being is perceived. It is understood that perceiving oneself as being is perceived. It is understood that perceiving oneself as poor is not an easy task, even if thpoor is not an easy task, even if the objective/material conditions point to it.e objective/material conditions point to it. Thus, perception Thus, perception and feeling encompass the meaning that people construct from their experiences of what it and feeling encompass the meaning that people construct from their experiences of what it means to be in poverty and how this affects their perspective of identity and their way of life. means to be in poverty and how this affects their perspective of identity and their way of life. The facThe facets of not being and not having, linked to selfets of not being and not having, linked to self--accountability, subjugate subjects to a accountability, subjugate subjects to a perspective of less worth. And the constant fear of not having, which seems to us to be a perspective of less worth. And the constant fear of not having, which seems to us to be a fundamental characteristic of subjective poverty. fundamental characteristic of subjective poverty.